Risk Management in SMEs: A Resilience-Based Approach for Business Sustainability - Setjoatmadja, Sylvia; Mujanah , Siti; Fianto , Achmad Yanu Alif (Journal of Economics and Management Scienties, 2025)
This study aims to examine the influence of risk management practices, financial literacy, and digital capability on business sustainability, with business resilience as a mediating variable in the context of small and medium enterprises (SMEs) in East Java, Indonesia. Using a quantitative approach, data were collected from 150 SME owners through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that all three independent variables have a significant positive effect on business sustainability, both directly and indirectly through business resilience. Among them, digital capability shows the strongest total effect. Furthermore, business resilience is confirmed to partially mediate the relationship between internal capabilities and sustainability outcomes. These findings highlight the critical role of resilience as a dynamic capability in sustaining SMEs under uncertain conditions. The study contributes to the development of a resilience-based sustainability framework and offers practical insights for policymakers and development agencies to design more integrated SME empowerment programs focusing on risk preparedness, financial competence, and digital transformation.